The influence of communication, motivation, and work discipline on performance of Indonesian cooperative University Employees - Fina Fahrina Fahrunisa; Gurawan Dayona Ismail; Yoyo Sudaryo; Fanji Wijaya; Recky Recky; Dadan Abdul Aziz (Sean Institute, 2024)
This research aims to analyze the relationship between the influence of Communication, Motivation and Work Discipline on Employee Performance at the Indonesian Cooperative University. In this research, the samples were employees at the University of Indonesia Developing with a sample size of 35 people. This research uses quantitative methods with non-probability sampling techniques (saturated samples), and data analysis tools using the SPSS version 25.0 program.